A rationally designed peptide IA-2-P2 against type 1 diabetes in streptozotocin-induced diabetic mice. (May 2017) - Shen, Lili; Lu, Shiping; Huang, Dongcheng; Li, Guoliang; Liu, Kunfeng; Cao, Rongyue; Zong, Li; Jin, Liang; Wu, Jie
Recent studies have investigated the potential of type 1 diabetes mellitus–related autoantigens, such as heat shock protein 60, to induce immunological tolerance or to suppress the immune response. A functional 24-residue peptide derived from heat shock protein 60 (P277) has shown anti-type 1 diabetes mellitus potential in experimental animals and in clinical studies, but it also carries a potential atherogenic effect. In this study, we have modified P277 to retain an anti-type 1 diabetes mellitus effect and minimize the atherogenic potential by replacing the P277 B epitope with another diabetes-associated autoantigen, insulinoma antigen-2 (IA-2), to create the fusion peptide IA-2-P2. In streptozotocin-induced diabetic C57BL/6J mice, the IA-2-P2 peptide displayed similar anti-diabetic effects to the control P277 peptide. Also, the IA-2-P2 peptide did not show atherogenic activity in a rabbit model. Our findings indicate the potential of IA-2-P2 as a promising vaccine against type 1 diabetes mellitus.